Effects of Turmeric oil, Sweetflag oil, and Margosan-O on the corn weevil Sitophilus zeamais Motsch - Dalugdug, Jose Wigan; Demayo, Cesar; Barrion, Adelina (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The toxicity of three botanical extracts, namely turmeric oil, sweetflagoil, and Margosan-O on the com weevil S. zeamais evaluated by determining percent mortality of the insects on each treatment. Amylase, acetylcholinesterase (ACTH), non-specific esterase activities, and total soluble proteins in treated insects were determined through spectrophotometry. The relative toxicity of the extracts are ranked as follows: tum,eric oil > sweetflag oil > Margosan-0. Turmeric oil reduced amylase activity most, and Margosan-O the '/east. ACTH production generally decreased in all of the treatments of oil derivatives, with turmeric oil causing the highest while Margosan-O showed the reverse. Non-specific esterase activities, generally increased. Esterases using beta-napthyl esters as substrate showed greater activity than using alpha-napthyl esters. Margosan-O induced the highest es/erase activity and turmeric oil the lowest. The total protein activity decreased as the concentration of the oil increased. Treatments with turmeric oil resulted to lowest protein content, followed by treatments with sweetflag oil and Margosan-0.